Морфогенез периферического отдела обонятельного анализатора лягушки озерной, Pelophylax ridibundus (Amphibia, Anura) - Ковтун, М.Ф.; Степанюк, Я.В. (Вестник зоологии, 2012)
By means of light microscopy method the features of lake frog, Pelophylax ridibundus (Pallas, 1771), basic olfactory epithelium were studied starting from the embryonal period till complete finishing of morphogenesis and transition to the land life. It is found, that during ontogeny frog nasal bags are differentiated into three parts. Besides the basic nasal cavity, which is covered by basic olfactory epithelium, during the period of metamorphosis additional cavities are created, namely medium and lower. Lake frog vomeronasal organ is located in the medial corner of the lower nasal cavity. Исследованы особенности морфогенеза основного обонятельного эпителия лягушки озерной, Pelophylax ridibundus (Pallas, 1771), начиная с эмбрионального периода до полного окончания метаморфоза и выхода на сушу. Установлено, что в онтогенезе носовые мешки лягушки озерной дифференцируют на три части. Кроме основной носовой полости, которая выстлана основным обонятельным эпителием, в период метаморфоза образуются дополнительные полости — средняя и нижняя. Вомерозональный орган у лягушки озерной размещен в медиальном углу нижней носовой полости.